2017
DOI: 10.1371/journal.pone.0183386
|View full text |Cite
|
Sign up to set email alerts
|

Development and feasibility of Inlife: A pilot study of an online social support intervention for informal caregivers of people with dementia

Abstract: BackgroundInformal caregivers of individuals with dementia have an increased risk to face social isolation due to progression of the disease. Online social media interventions might offer a new opportunity to increase access to social support and enhance positive interactions and openness in dementia care networks.ObjectiveThis explorative pilot study describes (1) the development of an online social support intervention Inlife, and (2) the evaluation of the feasibility of this intervention and the measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 38 publications
0
77
0
Order By: Relevance
“…Overall, of the 36 identified research papers, ten papers reported the assessment of a psychological outcome, however, there is limited evidence on psychological wellbeing impact as significant improvement was reported in only two of these studies (Boots et al, ; Marziali & Garcia, ) both of which were online interventions; 30 research papers reported on feelings of burden/anxiety/depression of these 19 stated a significant improvement (Andren & Elmståhl, ; Chenoweth et al, ; Chu et al, ; Easom et al, ; Finkel et al, ; Gaugler, Reese, et al, ; Gaugler et al, , , ; Hsu et al, ; Javadpour et al, ; Küçükgüçlü et al, ; Marziali & Garcia, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ); 20 papers provided findings from the assessment of health and well‐being, of these 11 had significant findings (Easom et al, ; Gaugler, Reese, et al, ; Hsu et al, ; Javadpour et al, ; Laakkonen et al, ; Marziali & Garcia, ; Mittelman et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ); six papers reported findings linked to carer satisfaction of which two produced significant findings (Andren & Elmståhl, ; Gaugler, Hobday, et al, ). Finally, 13 papers stated the findings from the assessed level of support, of these five reported significant improvement (Dam et al, ; Gaugler, Reese, et al, ; Marziali & Garcia, ; Wai Tong & Lee, ; Wang et al, ) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, of the 36 identified research papers, ten papers reported the assessment of a psychological outcome, however, there is limited evidence on psychological wellbeing impact as significant improvement was reported in only two of these studies (Boots et al, ; Marziali & Garcia, ) both of which were online interventions; 30 research papers reported on feelings of burden/anxiety/depression of these 19 stated a significant improvement (Andren & Elmståhl, ; Chenoweth et al, ; Chu et al, ; Easom et al, ; Finkel et al, ; Gaugler, Reese, et al, ; Gaugler et al, , , ; Hsu et al, ; Javadpour et al, ; Küçükgüçlü et al, ; Marziali & Garcia, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ); 20 papers provided findings from the assessment of health and well‐being, of these 11 had significant findings (Easom et al, ; Gaugler, Reese, et al, ; Hsu et al, ; Javadpour et al, ; Laakkonen et al, ; Marziali & Garcia, ; Mittelman et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ); six papers reported findings linked to carer satisfaction of which two produced significant findings (Andren & Elmståhl, ; Gaugler, Hobday, et al, ). Finally, 13 papers stated the findings from the assessed level of support, of these five reported significant improvement (Dam et al, ; Gaugler, Reese, et al, ; Marziali & Garcia, ; Wai Tong & Lee, ; Wang et al, ) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…In total 28 original studies were identified that tested an intervention comprising solely of peer support or had a peer support component. We examined the extent, nature and distribution of the studies included in this review and determined the following: the majority of studies ( n = 12) used a trial design including randomised controlled trials, pragmatic randomised trials, randomised controlled evaluations, randomised controlled two group design or randomised pilot studies (Charlesworth et al, ; Finkel et al, ; Gaugler et al, , , , ; Gaugler, Reese, Reese, & Mittelman, ; Hayden, Glynn, Hahn, Randall, & Randolph, ; Laakkonen et al, , ; Lai et al, ; Martindale‐Adams, Nichols, Burns, Graney, & Zuber, ; Mittelman et al, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ), eight studies used a pre/post‐test design (Boots, de Vugt, Withagen, Kempen, & Verhey, ; Chenoweth et al, ; Chu et al, ; Dam, van Boxtel, Rozendaal, Verhey, & de Vugt, ; Gaugler, Hobday, et al, ; Hsu et al, ; Javadpour, Ahmadzadeh, & Bahredar, ; O'Connor, Arizmendi, & Kaszniak, ), four a quasi‐experimental design (Andren & Elmståhl, , ; Easom, Alston, & Coleman, ; Marziali & Garcia, ; Pagán‐Ortiz, Cortés, Rudloff, Weitzman, & Levkoff, ), two a quasi‐experiment with mixed methods design (Baily, Kingsyon, Alford, Taylor, & Tolhurst, ; Küçükgüçlü, Akpınar Söylemez, Yener, & Işık, ) and the final two studies used mixed methods (Hattink, Droes, Sikkes, Oostra, & Lemstra, ; McKechnie, Barker, & Stott, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caring for a person living with dementia is also a demanding task that can lead to social isolation. Informal caregiving is regarded as a rewarding task, however; it can have a negative impact on a caregiver's well-being and quality of life [16]. Social recreational programs are increasingly becoming an essential intervention that can help promote the engagement of persons with dementia and their caregivers in the participation of social activities and involvement in community services [17].…”
Section: Overview Of Alzheimer's Disease and Social Isolationmentioning
confidence: 99%
“…This chapter examined the impact of social isolation on persons living with dementia and their caregivers. Researchers found that the risk for social isolation increases with age, and older people with dementia are particularly more vulnerable for developing loneliness and depression as a result of social isolation [16]. For instance, researchers have examined the negative emotional impact, such as loneliness as a result of the levels of social isolation in the lives of the persons with dementia and their carers [14,18].…”
Section: Future and Emerging Research Trendsmentioning
confidence: 99%